How do servant leadership and self-esteem at work shape family performance in China? A resource gain development perspective. Issue 3 (9th July 2021) - Li, Diwan; Li, Yanping; Hu, Yanghong; Tu, Yidong
Abstract : Purpose: Drawing on the resource gain development (RGD) perspective, this study is aimed to examine how servant leadership as an environmental resource and general self-esteem as a personal resource influence employees' family performance through work-to-family facilitation (WFF) and explore the moderating effects of gender and Chinese traditionality on the relationship between servant leadership and WFF. Design/methodology/approach: Two-wave data were collected from 369 employees in China. The structural equation model and path analysis were used to analyze the data. Findings: The results confirm that WFF mediates the effects of servant leadership and employees' general self-esteem on employees' family performance. Gender and Chinese traditionality moderate the relationship between servant leadership and WFF. Originality/value: This study contributes to existing research by revealing how specific environmental resources (servant leadership) and personal resources (general self-esteem) impact employee family performance through WFF; it also identifies gender and Chinese traditionality as demand characteristics which moderate the effect of environmental resources on WFF.